DESKRIPSI TINGKAT PENGETAHUAN IBU HAMIL TENTANG PREEKLAMPSIA DI PUSKESMAS KAMPAR KIRI KABUPATEN KAMPAR - maswarni maswarn; Trisiwi Kusumanigrum; Yeni yarnita; Pratiwi Gasri; Khusnul Khotimah (LPPM Universitas Abdurrab, 2023)
Preeclampsia is defined as the presence of a new onset of hypertension and proteinuria or other organ system disorders that occur at gestational age above 20 weeks. The Objective : To Know the Description Of The Level Of Knowledge Of Pregnant Women About Preeclampsia At The Kampar Kiri Health Center. The Research : This type of research used in this research is descriptive method. This research was conducted on 15-26 August 2022 at the Kampar Kiri Health Center, Kampar Regency. The population in this study were all pregnant women who visited the Kampar Kiri Health Center with a total of 48 respondents. The instrument used in this study was to distribute questionnaires to pregnant women who visited the Kampar Kiri Health Center. The results : Shows that from 48 respondents the majority of pregnant women knowledge about preeclampsia have sufficient knowledge 23 respondents (48.0%), good knowledge as many as 6 respondents (12.5%), and lack of knowledge as many as 19 respondents (39.5%). Conclusion : Respondents who visited the Kampar Kiri Health Center regarding the knowledge of pregnant women about preeclampsia the majority had sufficient knowledge with 23 respondents (48.0%))